THE VISA EXEMPTION POLICY IMPLEMENTATION ON GLOBAL MOBILITY: A STRATEGY TO MINIMISING THE RISKS AND MAXIMISING THE BENEFITS OF VISA POLICIES - Agung Sulistyo Purnomo (Polteknik Imigrasi, 2018)
To secure Indonesian borders and uphold state’s sovereignty, the Directorate General of Immigration (Imigrasi) must develop an effective monitoring strategy. Managing people’s mobility within the Indonesian territory should also be the main concern of the current government amidst the implementation of the visa waiver policy. This means that the economic benefit expected from the free-visa policy must not undermine the national security. In particular, this study argues that the visa exemption policy is not related to the rise of immigration violations and, therefore, the level of immigration offense is influenced by other factors including poor management and scrutiny of foreign arrivals. This paper will analyse secondary data to deeply understand what challenges faced by Imigrasi during the implementation of President Regulation No. 21 of 2016 about the visa waiver for 169 countries. The data was originally obtained through interviews, surveys, research, and reports published by academic researchers or government/non-government agencies. This method is utilised as a means to gather all relevant information related to the topic discussion, especially, in finding the urgency for reform and adjusting Imigrasi’s policy direction. The result conveys that visa exemption regulation needs to be reviewed immediately.